Benny Wenda’s Political Propaganda about the Free Papua Issue Through Twitter - Zahidi, M. Syaprin (SCAD Independent, 2023)
The purpose of this study was to explain the political propaganda of the free Papua issue spread by Benny Wenda via his Twitter account. This study used a qualitative approach to analyze Benny Wenda's Twitter account. The NVivo 12 Plus software was used in this study because it can process Benny Wenda's Twitter data. This research discovered Benny Wenda's Twitter propaganda of the free Papua issue divided into 11 important topics, namely